1999
DOI: 10.1046/j.1365-2249.1999.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of dendritic cells (DC)ex vivostimulated with interferon-gamma (IFN-γ) down-modulates autoimmune diabetes in non-obese diabetic (NOD) mice

Abstract: The NOD mouse has been used to explore the many features of insulin-dependent diabetes mellitus (IDDM) that is caused by the destruction of insulin-producing beta cells in the islets of Langerhans of the pancreas. Self-reactive T cells have been considered to mediate IDDM in the NOD mouse, and antigen-presenting cells like DC and macrophages are expected to be involved in the processes from their role in generating regulatory or effector T cells. The present study shows that transfer of IFN-gamma-stimulated DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 39 publications
6
71
1
Order By: Relevance
“…Studies in other autoimmune diseases such as experimental autoimmune encephalomyelitis and collagen-induced arthritis also reported on a specific prevention of disease development after DC vaccination [17,40,41]. However, in contrast to our observation, previous studies have shown an autoantigen-unspecific protection from diabetes after transfer of DCs in NOD mice [19,20,21]. These inconsistent results could be due to differences in the origin of the DCs, the culture condition chosen and the pre-treatment with IL-10.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Studies in other autoimmune diseases such as experimental autoimmune encephalomyelitis and collagen-induced arthritis also reported on a specific prevention of disease development after DC vaccination [17,40,41]. However, in contrast to our observation, previous studies have shown an autoantigen-unspecific protection from diabetes after transfer of DCs in NOD mice [19,20,21]. These inconsistent results could be due to differences in the origin of the DCs, the culture condition chosen and the pre-treatment with IL-10.…”
Section: Discussioncontrasting
confidence: 99%
“…Protection from diabetes was observed in NOD mice after immunisation with DCs from the local pancreatic lymph nodes [17]. In addition, intraperitoneal injection of DCs isolated from the spleen or bone marrow was found to reduce the incidence of diabetes in NOD mice whether or not the DCs were pulsed with autoantigen [19,20,21]. The unspecific immunomodulatory effect has been explained by a general activation of Th2 cells following DC administration.…”
mentioning
confidence: 99%
“…These include the use of cultured, bone marrow-derived DCs to prevent T1D (14), genetic manipulation of DCs to prevent T1D or collagen-induced arthritis (16,17), or exposure to immunomodulators including TNF-␣ (18) or TGF-␤ (24) to prevent experimental autoimmune encephalitis and experimental autoimmune myasthenia gravis, respectively. In particular, exposure ex vivo to IFN-␥ has been shown to generate DCs that ameliorate experimental autoimmune encephalitis (25) or T1D (15). Given the sustained high levels of IFN-␥ production we have shown in the spleen, PLN, and pancreas of NOD mice after S. typhimurium infection (4), our observations may represent an important in vivo correlate.…”
Section: Discussionmentioning
confidence: 58%
“…Observations suggest that only a small fraction of labeled DCs can be recovered from major organs 24 h after injection, presumably representing a high level of cell death after transfer (T. Raine, unpublished observations) (15). Overall, it seems that the number of injected DCs that traffic to the PLN is probably very small indeed.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that the active metabolite of vitamin D can induce TDCs that inhibits NOD mice diabetes development by increasing the function of Tregs (Adorini, Penna et al 2003). Furthermore, DCs treated ex-vivo with IFN-, a pleiotropic cytokine with both immunostimulatory and immunoregulatory functions, act in an immunosuppressive manner after in vivo transfer (Shinomiya, Fazle Akbar et al 1999). Such IFN--treated TDCs were demonstrated to successfully migrate into the pancreas and associated lymphoid tissues, an important feature desired in the generation of both DCs as positive (tumor vaccines) and negative vaccination tools.…”
Section: Tdcs In Autoimmune Disease Studies 411 Type 1 Diabetesmentioning
confidence: 99%